Evaluasi Program Akademi Desa 4.0 dengan Model CIPP di Kementerian Desa, Pembangunan Daerah Tertinggal dan Transmigrasi - Rizqiyana Rizqiyana; Nur Saidah; Pujiono Pujiono (AS-SABIQUN, 2022)
This study aims to determine the evaluation of the Akademi Desa 4.0 program with the CIPP model at the Ministry of Villages, Development of Disadvantaged Regions and Transmigration. The focus of this research is elaborated into several research problem formulations, including: 1) How to evaluate the context of the Akademi Desa 4.0 program 2) How to evaluate the input of the Akademi Desa 4.0 program 3) How to evaluate the Akademi Desa 4.0 program process and 4) How to evaluate the Akademi Desa 4.0 program product. This research method uses qualitative research with the type of field research (field research) by collecting data through observation, interviews and documentation. The data analysis technique in this research is descriptive analysis method. The results of the study can be concluded that the evaluation results above indicate that, in terms of context, the Akademi Desa 4.0 program at the Ministry of Villages, Development of Disadvantaged Regions and Transmigration is indeed very much needed by the village, especially the community in managing themselves. In terms of input, the Akademi Desa 4.0 program has been prepared to meet the needs of the community and has been supported by human resources (HR), funding, and adequate infrastructure. In terms of the process, the Akademi Desa Work program 4.0 is carried out based on management functions, namely: planning, organizing, monitoring, and evaluating. In terms of products, in general, the programs at the Akademi Desa 4.0 can be said to have been achieved even though they have not been maximized, so there needs to be improvements in their implementation.